2014
DOI: 10.3109/02699052.2014.947619
|View full text |Cite
|
Sign up to set email alerts
|

Assessment practices of speech-language pathologists for cognitive communication disorders following traumatic brain injury in adults: An international survey

Abstract: These findings have implications for training of SLPs in a more diverse range of assessment tools for this clinical group. The findings raise questions regarding the statistical validity and reliability of assessments currently used in clinical practice. It highlights the need for further research into how SLPs can be supported in translating current evidence about the use of assessment tools into clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 36 publications
3
42
0
Order By: Relevance
“…Frith et al . (2014) report on 265 speech pathologists’ practices in five countries in the management of cognitive communication deficits in people with traumatic brain injury. Here they found that 44.3% of clinicians reported routinely assessing discourse; more experienced clinicians (> 10 years’ experience) were more likely to assess discourse; and that discourse and/or pragmatic skills assessment was significantly more likely to be conducted in the community setting, compared with other settings (Frith et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Frith et al . (2014) report on 265 speech pathologists’ practices in five countries in the management of cognitive communication deficits in people with traumatic brain injury. Here they found that 44.3% of clinicians reported routinely assessing discourse; more experienced clinicians (> 10 years’ experience) were more likely to assess discourse; and that discourse and/or pragmatic skills assessment was significantly more likely to be conducted in the community setting, compared with other settings (Frith et al .…”
Section: Introductionmentioning
confidence: 99%
“…Here they found that 44.3% of clinicians reported routinely assessing discourse; more experienced clinicians (> 10 years’ experience) were more likely to assess discourse; and that discourse and/or pragmatic skills assessment was significantly more likely to be conducted in the community setting, compared with other settings (Frith et al . 2014). Interestingly, though, clinicians appeared to be primarily assessing discourse as pragmatic skills using formal assessments of perceived communicative ability and social perception, rather than undertaking linguistic discourse analysis, for example, word counts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…) can be difficult to diagnose (Frith et al . ) and typically persist for many years post‐injury (Bond and Godfrey ).…”
Section: Introductionmentioning
confidence: 99%